Assessment of indoor air quality : a study in selected level of Tun Abdul Razak 1 Library, Uitm Shah Alam / Kamal Azwan Kamarun - Kamarun, Kamal Azwan (Faculty of Applied Sciences, 2006)
Library is of one the most frequent place visited by university students everyday. Many students favor to spend their time in library especially during exam season. Good indoor air quality, therefore very essential to library users. Various methods are required to achieve healthy indoor conditions for library users. This is important for understanding current condition and examining relationship between indoor environment and human health. The study was carried out at four sampling points in level 5 of PTAR 1 Library, UiTM Shah Alam. The study presents the current lAQ status of the four sampling points using an AQ 5000 Pro and Airmetrics MiniVol Portable Air Sampler. The data was collected for an eight hour measurement. The parameters measured were carbon dioxide (CO2), carbon monoxide (CO), relative humidity (RH), temperature and respirable particulate matter (PMio). This study aims to provide current profiles and to illustrate the level of various indoor pollutants depending on the human loads, types of activities, the size of the floor and thermal comfort in the library. Result showed that the concentration of CO2 and particulate matter (PMio) was below the recommended limit by Malaysia Code of Practice on Indoor Air Quality (2005). This result however was significantly affected by the average number of occupants, the types of activities and the size of the floor in the library. However, thermal comfort in the selected sampling points was exceeding the comfortable limit recommended by previous study. The thermal comfort was insufficient in providing a comfortable and healthy environment to the library users based on the temperature humidity index (THI). The carbon monoxide (CO) however was not being detected in this study due to its low probability to exist in the library